(3QSGdI aj GdJhMjOs - (3jMji Hf CHj HcQ GdMfajs
(3ChdgG (B:s
(3GdMeO ddg GdeJhMO HCRdi GdhLhO hGdPGJ CeG HYO ajbhd GdYHO jMji Hf CHj HcQ GdMfai deG EJab efi JCdja eNJUQ HGdaGQSjI ai HjGf GdEYJbGO SCd efi LeGYI ef GdWdHI hGdNdGf Cf CcJH s
(3BNQgG (B:s
(3hdh CfgG bGdJ dRhLgG jG jghOi Ch jG eLhSi abGd Ef cfJ gcPG dGJScfi eYi bGd HYVge JcaQ hbGd HYVge dGJcaQ s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdJhMjO hGdedd hGdfMds